Make this! : building, thinking, and tinkering projects for the amazing maker in you - Schwartz, Ella, 1974- (National Geographic kids., 2019)
Presents a collection of over forty projects designed to engage young readers in a variety of scientific and engineering topics including systems, optics, energy, acoustics, forces, and motion. Includes material lists, step-by-step instructions, and color photographs.